Clinical significance of dynamics between oxidative stress levels during mechanical lung ventilation in premature infants with persistent pulmonary hypertension - Klymenko, Tetiana; Kononovych, Mariia (ScienceRise: Medical Science, 2022)
The aim of this study was to determine the clinical significance of the levels and dynamics of the urinary 8-hydroxy-2-deoxyguanosine, degree of pulmonary hypertension on choosing the duration and form of respiratory support in premature infants with respiratory distress syndrome in combination with perinatal asphyxia. Materials and methods. The levels of the urinary 8-hydroxy-2-deoxyguanosine (8-OHdG), ng/ml were determined by enzyme immunoassay (ELISA) method and the degree of pulmonary hypertension (PH) - by echocardiography in 60 premature new-borns at 26-32 weeks of gestation on the 1st and the 3rd–5th days of life. A comparative analysis of indicators was carried out in 2 groups: I – 32 children with respiratory distress syndrome (RDS); II – 28 children with RDS combined with perinatal asphyxia. All infants received a respiratory support, depending on the clinical condition, blood gas analyses, and the chest X-ray. Results. The level and dynamics of the urinary 8-OHdG correlated to degree of PH, form, and duration of respiratory support. Children of the group II on the 1st day of life had echocardiogram indicators of mild PH and indicators of the urinary 8-OHdG 2.27±0.39 ng/ml; by 3rd–5th days of life – level of the urinary 8-OHdG increased to 4.10±0.42 ng/ml and the level of PH – to moderate, required 76.2 % longer respiratory support compared to children of the group I. Conclusions. Prematurely born infants with RDS in combination with perinatal asphyxia have a higher oxidative stress (OS) levels and more significant pulmonary hypertension, which requires a longer respiratory support by 76.2 % and more often use of high frequency oscillatory ventilation (HFOV) by 9.3 %